Profil Penderita Anemia Aplastik di RSUP Dr. M. Djamil Padang Tahun 2018-2019 - Amanda Rizki; Zelly Dia Rofinda; Gusti Revilla (Fakultas Kedokteran, Universitas Andalas, 2021)
Background. Aplastic anemia is a failure of the process of formation and development of blood cells that causes a decrease or absence of hematopoietic precursor cells in the bone marrow. Although the prevalence of this disease is rare, aplastic anemia has the potential to cause death with risk factors that are easily found in everyday life and are rarely realized.Objective. To determine the profile of patients with aplastic anemia at General Hospital Dr M Djamil Padang.Methods. This is a descriptive retrospective study. The population of this study are all patients diagnosed with aplastic anemia by clinicians in the Medical Record Installation of Dr. M. Djamil Hospital, Padang, between 1 January 2018 - 31 December 2019..Results The results showed that 21.57% patients with aplastic anemia were at the age of 56-65 years and the incidence was higher in women than men. The highest risk factor was exposure to chemical and insecticides (18.62%), but 54.9% of the data did not include risk factors. 31.37% work as students. 67.65% suffered from mild aplastic anemia, 60.78% were on immunosuppressive therapy, and 65.69% had partial remission outcomes.Conclusion. The majority of patients with aplastic anemia based on age are 56-65 years and based on gender, the incidence is higher in women. The most common risk factors were exposure to chemical and insecticides. . The most common level of severity is non-severe aplastic anemia. The most common type of therapy is immunosuppressive therapy. The most common outcome is partial remission.